Education, health and mortality: Evidence from a social experiment - Costas Meghir; Mårten Palme; Emilia Simeonova (Institute for the Study of Labor (IZA), 2012)
We study the effect of a compulsory education reform in Sweden on adult health and mortality. The reform was implemented by municipalities between 1949 and 1962 as a social experiment and implied an extension of compulsory schooling from 7 or 8 years depending on municipality to 9 years nationally. We use detailed individual data on education, hospitalizations, labor force participation and mortality for Swedes born between 1946 and 1957. Individual level data allow us to study the effect of the education reform on three main groups of outcomes: (i) mortality until age 60 for different causes of death; (ii) hospitalization by cause and (iii) exit from the labor force primarily through the disability insurance program. The results show reduced male mortality up to age fifty for those assigned to the reform, but these gains were erased by increased mortality later on. We find similar patterns in the probability of being hospitalized and the average costs of inpatient care. Men who acquired more education due to the reform are less likely to retire early.
urn:nbn:de:101:1-201208065448
Keywords: I12; I18; I21; 330; causal effects of education; compulsory schooling laws; comprehensive school reforms; education reform; returns to schooling; Schulbesuch; Bildungsreform; Bildungsertrag; Gesundheit; Sterblichkeit; Schweden